Proposed new interior design of Gallery Batik for Noor Arfa Batik at The Red Bungalow, No 153 Jalan Ampang, 50450 Ampang, Kuala Lumpur / Fatin Norfasya Rosli - Rosli, Fatin Norfasya (Faculty of Architecture, Planning and Surveying, 2011)
This report is on Proposed New Interior Design of Gallery batik for Noor Arfa Batik who are the largest name in batik industries in Malaysia mostly include international level. The idea to proposed this project is because Noor Arfa was famous name in developing Batik at Malaysia which is produced at Terengganu. The report will elaborate on the reason of preserving and developing batik, one of the most important heritages in Malaysia. The suggested location for this project is located at The Red Bungalow, no 153 jalan Ampang, 50450 Ampang, Kuala Lumpur. This place usually busy with business activity, many people including tourist are always came here to visit and it has been a main destination when came to Malaysia. So that I proposed to introduce a new interior design of the gallery at this place because of the strategic location where the market was so good. This research was executed through library research by using books, journals, newspapers and internet articles. It has been found that batik have regain its rise and become one of the main attraction of Malaysian craft and textile. Beside bring Malaysia’s name to the international level, batik industry also add more income to the country. In conclusion, it is recommended that more studies should be done in this field so that the preservation and development of batik can be done.